Mouse Ether: Accelerating The Acquisition Of Targets Across Multi-Monitor Displays - Baudisch, Patrick; Cutrell, Ed; Hinckley, Ken; Gruen, Robert (CHI '04: CHI '04 extended abstracts on Human factors in computing systems, 2004)
When acquiring a target located on a different screen, multi-monitor users face a challenge: differences in resolution and vertical and horizontal offsets between screens cause the mouse pointer to get warped, making the attempt to acquire the target difficult. Mouse ether eliminates warping effects by applying appropriate transformations to all mouse move events. In our user study, mouse ether improved participants’ performance on a target acquisition task across two screens running at different resolutions by up to 28%. 7 of the 8 participants also strongly preferred using mouse ether to the control.